Fumaric acid esters in the management of psoriasis - Balak DMW (Dove Medical Press, 2015)
Deepak MW Balak Department of Dermatology, Erasmus Medical Center, Rotterdam, the Netherlands Abstract: Fumaric acid esters (FAE) are small molecules with immunomodulating, anti-inflammatory, and anti-oxidative effects. FAE were introduced as a systemic psoriasis treatment in 1959 and empirically developed further between 1970 and 1990 in Germany, Switzerland, and the Netherlands. The development of FAE as psoriasis treatment did not follow the traditional drug development phases. Nonetheless, in 1994 FAE were approved in Germany for the treatment of severe plaque psoriasis. FAE are currently one of the most commonly used treatments in Germany, and FAE are increasingly being used as an unlicensed treatment in several other European countries. To date, six randomized controlled trials and 29 observational studies have evaluated FAE in a combined total of 3,439 patients. The efficacy and safety profile of FAE is favorable. About 50%–70% of patients achieve at least 75% improvement in psoriasis severity after 16 weeks of treatment. Common adverse events of FAE include gastrointestinal complaints and flushing symptoms, which lead to treatment discontinuation in up to 40% of patients. Lymphocytopenia, eosinophilia, and proteinuria are commonly observed during FAE treatment, but rarely require treatment discontinuation. The long-term safety profile of continuous FAE treatment is favorable without an increased risk for infections, malignancies, or other serious adverse events. There are no known drug-interactions for FAE. The 2009 European evidence-based S3-guidelines on psoriasis treatment recommend FAE and suggest it as a first-line systemic treatment for moderate-to-severe plaque psoriasis. This review is aimed to give an overview of FAE treatment in the management of psoriasis. Keywords: fumaric acid esters, fumarates, dimethyl fumarate, Fumaderm, psoriasis, systemic treatment